Use of cryptographic technologies for privacy protection of watermarks in internet retails of digital contents. (3rd April 2006) - Wang, Changjie; Leung, Ho-fung; Cheung, S.C.; Wang, Yumin
In this paper, we propose a scheme of secure watermarking protocol using cryptographic technologies for use in real life internet retail market of digital contents, in which trust between customers and digital contents providers may not be assumed. A commutative encryption algorithm is used in our scheme to doubly lock the information by the secret keys of both a contents provider, and its customer, separately. The privacy of watermark pattern is maintained while the digital rights of the contents provider are protected. This is achieved by allowing the customer to choose a secret pattern of watermark combination unknown to the contents provider. Consequently, the quality of the watermarked digital contents can be guaranteed. We show that the protocol is secure against any possible attacks from the customer and the contents provider. Moreover, the disputes resolution process becomes mechanical.